(untitled) (Research, Society and Development, 2021)
Auriculotherapy, an acupuncture microsystem, is a major therapeutic method in pain treatments. The use of its practice within traditional Chinese medicine dates back to decades, where stimuli are made in certain areas of the ear, and these are reflected in the body. This study was a descriptive bibliographical research that has as general objective to carry out a literature review where it can be identified as auriculotherapy is used as a therapeutic process of analgesia in cases of pain, and for specific objectives to verify the effectiveness of treatment with auriculotherapy in pain ; define which pinna points are most used; and mention the means used to stimulate the points. Data collection was performed, based on 7 articles found in a digital database (Google Academic and SciELO), in a systematic way and placed in a table. It was found through the analysis that there was great significance in the use of auriculotherapy as a method of analgesia.